Community-based mobile tuberculosis clinics in rural Madagascar: impact and cost-effectiveness analysis - Beigel, Lukas; Nguyen, Hoa Thi; De Allegri, Manuela; Franke, Mara Anna; Randrianantoanina, Antsa; Ranjaharinony, Fierenantsoa; Etrahagnane, Miandrisoa; Knauss, Samuel; Emmrich, Julius; Muller, Nadine (BMJ global health, 2025)
Introduction Tuberculosis (TB) remains an important public health challenge globally. Madagascar faces a substantial TB burden despite enhanced efforts from its national TB control programme. This necessitates innovative and context-specific TB prevention and care interventions that are both impactful and cost-effective. We evaluated the effectiveness and cost-effectiveness of a community-based mobile TB clinic intervention in a remote rural area of Madagascar, addressing specific access barriers and implementation challenges.Methods The analysis employed an interrupted time series analysis (ITSA) comparing the intervention to the standard national TB control programme (NTP) to assess the effectiveness of the intervention in increasing TB case detection rates. A decision tree model was used to evaluate the cost-effectiveness of the intervention from a healthcare provider perspective when compared with the NTP. The study incorporated one-way sensitivity analyses and Monte Carlo simulations with 10 000 iterations to generate the probability distribution of estimates and uncertainty ranges.Results The ITSA found that the intervention cumulatively increased TB case detection 2.88-fold compared with the control group over the 27-month study period. The probability for a patient to successfully complete TB treatment in the intervention group was 97%, compared with 91% in the control group. Incremental costs per person with TB were $ 316. With an incremental cost-effectiveness ratio (ICER) of $ 25 per disability-adjusted life year averted, well below the $ 96 cost effectiveness threshold for Madagascar, the intervention was highly cost-effective. Importantly, the ICER remained robust throughout sensitivity analyses, reaching a maximum of $ 67.Conclusion The study underscores the importance of community-based interventions for TB and calls for policymakers to prioritise and scale up such interventions, both in Madagascar and in other low-income countries with similar access-related challenges.
Veröffentlicht: 29. Oktober 2025
Gesehen am 05.12.2025